Constraining structural dip and magnetization direction of a sheet from its static and dynamic magnetic anomalies. Issue 1 (1st December 2019) - Foss, Clive; Clark, David; Keenan, Shane; Leslie, Keith
Summary: Following advances in magnetometer instrumentation and inversion software we re-explore the feasibility of a field methodology utilising relationships between magnetization and dynamic (time-variation) magnetic field anomalies to recover structural information from magnetic field data over thin sheets. We show that we can estimate the dip of a sheet from a reliably determined dynamic magnetic anomaly induced by the range of the magnetic field through its diurnal variation. The strength and inclination of remanent magnetization in the plane perpendicular to the sheet can be subsequently estimated from the static magnetic anomaly using that pre-determined dip angle. The principal challenge in working with dynamic magnetic anomalies is their low amplitude and the requirement for multiple measurements at each station. These relationships between magnetizations and fields apply equally to field gradients. SQUID magnetometers and gradiometers can provide a feasible solution to the high resolution measurements required for this application